Towards a New Enlightenment - The Case for Future-Oriented Humanities - Gabriel, Markus (THE NEW INSTITUTE.Interventions, 2022)
What role can the humanities play in shaping our common future? What are the values that guide us in the 21st century? How can we unleash the potential the humanities offer in a time of multiple crises? This volume tackles some of these fundamental questions, acknowledging and developing the changing role of academic discourse in a turbulent world. This timely book argues that the humanities engender conceptual tools that are capable of reconciling theory and practice. In a bold move, we call for the humanities to reach beyond the confines of universities and engage in the most urgent debates facing humanity today - in a multidisciplinary, transformative, and constructive way. This is a blueprint for how societal change can be inclusive and equitable for the good of humans and non-humans alike.